2021
DOI: 10.11604/pamj.2021.38.113.27601
|View full text |Cite
|
Sign up to set email alerts
|

Sudden death complicating a coronary arteritis: polyarteritis nodosa (case report)

Abstract: Coronary artery aneurysms are uncommon, are usually associated with atherosclerosis, and rarely involve all three major coronary arteries. Data on the optimal choice of acute myocardial infarction (AMI)´s revascularization in the context of polyarteritis nodosa (PAN) is limited to case reports and is still an open question. The present report describes a rare case of a young male patient followed for PAN presenting with acute myocardial infarction (AMI). Coronary angiography revealed multiple severe aneurysmal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…However, a recent case report of AMI in a young patient with PAN demonstrated the use of PCI following a high dose of steroid management. It concluded careful monitoring of coronary arteries during the chronic phase of PAN [21]. The study also reported sudden cardiac death of the patent, likely due to stent thrombosis [21].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, a recent case report of AMI in a young patient with PAN demonstrated the use of PCI following a high dose of steroid management. It concluded careful monitoring of coronary arteries during the chronic phase of PAN [21]. The study also reported sudden cardiac death of the patent, likely due to stent thrombosis [21].…”
Section: Discussionmentioning
confidence: 81%
“…It concluded careful monitoring of coronary arteries during the chronic phase of PAN [21]. The study also reported sudden cardiac death of the patent, likely due to stent thrombosis [21]. Given the limited literature, we are unable to determine long-term survival rates after PCI in AMI with vasculitis and this requires more longitudinal studies.…”
Section: Discussionmentioning
confidence: 98%
“…Una manera que se ha evidenciado para diferenciarla de otras vasculitis es mediante el resultado de ANCA séricos negativos. (Chercoles y Fong, 2016;Helfgott y Bhattacharyya, 2022;Zahoor et al, 2022;Gaviria et al, 2020, Naidu et al, 2021 -Imágenes: Angiorresonancia, Angiotomografía y/o Angiografía en las que se pueden observar dilataciones o estrechamientos de las arterias afectadas (Munera-Campos et al, 2020;Gabsi et al, 2021) como lo es la presencia de micro aneurismas, los cuales son distintivos de la PAN. (Wuelan, 2022) -Biopsia: se observa vasculitis leucocitoclástica de arterias de mediano calibre, necrosis de las paredes del vaso, asociado a marcada inflamación perilesional (Jennette, 2013;Sociedad Argentina de Reumatología, 2022), la biopsia debe centrarse sobre un nódulo sensible o una lesión purpúrica (Michelitti, 2022).…”
Section: Introductionunclassified